Nasal mucosa changes in students exposed to formaldehyde vapour - Sherwani, R. (Springer India, 2002)
Formaldehyde has been used since ages in the various laboratories. Recently, interest has developed in the possible role of formaldehyde in the development of Squamous Cell Carcinoma. In this study 53 students (undergraduates and postgraduates) were exposed to formaldehyde and they were compared with 25 students (control group) unexposed to formaldehyde. Results have shown that students who were exposed to formaldehyde for a longer time showed mucosal changes as compared to the control group.